Answer:
x = -
, x =
![(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/810xodspel5mrswej0fay1vvz0sburw3kp.png)
Explanation:
Given
x² - x -
= 0
Multiply through by 4 to clear the fraction
4x² - 4x - 3 = 0
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term
product = 4 × - 3 = - 12 and sum = - 4
The factors are + 2 and - 6
Use these factors to split the x- term
4x² + 2x - 6x - 3 = 0 ( factor the first/second and third/fourth terms )
2x(2x + 1) - 3(2x + 1) = 0 ← factor out (2x + 1) from each term
(2x + 1)(2x - 3) = 0
Equate each factor to zero and solve for x
2x + 1 = 0 ⇒ 2x = - 1 ⇒ x = -
![(1)/(2)](https://img.qammunity.org/2021/formulas/physics/middle-school/ukxexrkoplrwscaxd96qbbkphc5fo6w2ur.png)
2x - 3 = 0 ⇒ 2x = 3 ⇒ x =
![(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/810xodspel5mrswej0fay1vvz0sburw3kp.png)